Does Preoperative Halo-Gravity Traction Reduce the Degree of Deformity and Improve Pulmonary Function in Severe Scoliosis Patients With Pulmonary Insufficiency? A Systematic Review and Meta-Analysis - Yang, Zhao; Liu, Yang; Qi, Longtao; Wu, Shanshan; Li, Jingwen; Wang, Yu; Jiang, Bin (Frontiers in Medicine, 2021)
Background: Halo-gravity traction is a commonly used clinical intervention to reduce surgical risk in patients with scoliosis before surgical correction. Some previous studies have focused on the application of halo-gravity traction on patients with severe spinal deformity and pulmonary insufficiency, but the overall effect of halo-gravity traction has not been fully understood. The object of the present study was to perform a meta-analysis exploring the efficacy of preoperative halo-gravity traction on radiographic measurement and pulmonary function in severe scoliosis patients with pulmonary insufficiency. Methods: We searched the medical works of literature completed before January 17, 2021, in the databases of Pubmed, Embase, and Cochrane Library. Studies that quantitatively analyzed the effects of halo-gravity traction on the deformity and pulmonary functions of patients with severe scoliosis were included. Two researchers independently conducted the literature search, data extraction, and quality assessment. We used the Review Manager Software (version 5.4) for statistical analysis and data analysis. Mean difference (MD) with 95% confidence intervals (CIs) were calculated to evaluate the effects of halo-gravity traction. Results: Seven studies involving 189 patients received halo-gravity traction therapy preoperatively were analyzed in our study. Preoperative halo-gravity traction significantly ameliorated the degree of deformity in severe scoliosis patients with pulmonary insufficiency, especially reduced coronal Cobb angle and sagittal Cobb angle effectively [mean deviation (MD) = 2 7.28 (95%CI 21.16–33.4), p < 0.001; MD = 22.02 (95%CI 16.8–27.23), p < 0.001]. Preoperative halo-gravity traction also improved the pulmonary functions in patients, especially increasing %FVC and %FEV1 [MD = −0.0662 (95%CI −0.0672–−0.0652), p < 0.001; MD = −0.0824 (95%CI −0.0832–−0.081), p < 0.001]. Conclusions: Preoperative halo-gravity traction for severe scoliosis patients shows significant improvement in the degree of deformity and pulmonary functions. Halo-gravity traction is an effective method to improve the tolerance of patients to surgery in the perioperative period.